New strategy for enhancing Savonius turbine efficiency through delayed flow separation with advanced flow control - Mohd Safie, Abdullah; M. Shukur, Zainol Abidin; F., Ismail (Elsevier, 2025)
This study introduces a novel active flow control method for Savonius wind turbines using suction cavities to enhance the aerodynamic performance. The primary objective is to delay flow separation on the convex side of the advancing blade at specific azimuthal angles during rotation. Flow separation in this region, caused by adverse pressure gradients, typically limits the effective area for lift generation, reducing torque and efficiency. By implementing suction cavities that extract air from the blade surface, the flow remains attached further toward the blade root, thereby widening the surface area over which lift is generated. Computational fluid dynamics (CFD) simulations were conducted to validate the effectiveness of the proposed method. The rotor with suction cavities (optimized case) demonstrated a significant improvement in the coefficient of power (CP) compared to the base rotor performance. The optimized case achieved a Cp of 0.546 at a tip-speed ratio (TSR) of 0.9 and reached a peak CP of 0.622 at TSR = 1.01, exceeding the theoretical Betz limit due to the introduction of external energy through an active flow control. Analysis of pressure and velocity contours revealed that the suction cavities create a low-pressure region along the convex surface, enhance flow attachment, and increase lift forces and torque generation. The findings indicate that the use of suction cavities as an active flow control mechanism is effective in enhancing the efficiency of Savonius turbines.